Print Culture, Agency, and Regionality in the Hand Press Period
XIX, 275 p. 18 illus.
Keywords: “This collection exemplifies the advances in the intellectual domain of book history in recent decades. There are new insights here for scholars and students not only of book history but also for other cultural, social and economic historians.” —John Feather, Loughborough University “This highly engaging and multifaceted collection of essays addresses in exciting new ways British regional histories of printing and bookselling in the hand press period from the mid-fifteenth to the early nineteenth century. By focusing on the agency of place in writing, production and distribution, contributors vividly illuminate the interactions between trades and communities and the legislative and institutional structures governing them, but also how those involved in regional printing and book trades created particular and often widely influential narratives about their regions. This welcome re-evaluation of regional print production challenges and reinvigorates the whole history of print in Britain across more than four centuries.” —James Raven FBA, Fellow of Magdalene College, University of Cambridge Print Culture, Agency, and Regionality in the Hand Press Period illuminates the diverse ways that people in the British regional print trades exerted their agency through interventions in regional and national politics as well as their civic, commercial, and cultural contributions. Works printed in regional communities were a crucial part of developing narratives of local industrial, technological, and ideological progression. By moving away from understanding of print cultures outside of London as ‘provincial’, however, this book argues for a new understanding of ‘region’ as part of a network of places, emphasising opportunities for collaboration and creation that demonstrate the key role of regions within larger communities extending from the nation to the emerging sense of globality in this period. Through investigations of the men and women of the print trades outside of London, this collection casts new light on the strategies of self-representation evident in the work of regional print cultures, as well as their contributions to individual regional identities and national narratives. Rachel Stenner is Senior Lecturer in English Literature in the School of Media, Arts, and Humanities, University of Sussex, UK. She is the author of The Typographic Imaginary in Early Modern English Literature (2018) and co-editor of the collection of essays Rereading Chaucer and Spenser: Dan Geffrey with the New Poete (2019). Kaley Kramer is Deputy Head of English at Sheffield Hallam University, UK. She is the co-editor of Women During the English Reformations (Palgrave 2014) and Time, the City, and the Literary Imagination (Palgrave 2020). Adam James Smith is Senior Lecturer in Eighteenth-Century Literature at York St John University, UK. He works on cheap eighteenth-century political print, with a particular interest in works of protest and satire. Smith has published on Joseph Addison, James Montgomery and Eliza Haywood.